Synthesizing, Characterizing and Studying the Biological Activity of Some New Schiff-Bases Derivatives Containing the Monosaccharide Moiety (Baghdad Science Journal, 2016)
A new series of ?-D-glucose as Schiff bases derivatives is synthesized and characterized with studying their bioactivity. Hydroxyl groups at C (1,2&5,6) sugar moiety are converted into acetal form through a reaction with dry acetone using phosphoric acid and anhydrous zinc chloride as catalysts producing 1,2:5,6-di-O-isopropyledine ?-D-glucofuranose(I). The five memberd ring acetal of C(5,6) is hydrolyzed with acetic acid (65%)and a reaction of the new product with sodium periodate is carried on to get an aldehyde moiety which is used to produce a new series of Schiff bases through reacting with different amino compounds such as 4-amino antipyrene . The suggested chemical structures of the prepared compounds are confirmed by using UV., FT-IR and1 H-NMR spectra .Most of the prepared compounds show antibacterial activity.